Research and application of anti-icing technology for medium and low speed maglev trains - WU Zhihui; TONG Laisheng; LUO Huajun; GAO Feng; WANG Jiaheng (机车电传动)
Medium-low speed maglev trains typically operate in elevated mode and have unique suspension systems and track structures that are different from traditional wheel-rail systems. As a result, these trains are more susceptible to the impacts of snowy and icy weather when running on elevated tracks. The article conducted research and analysis on the actual operation of medium-low speed maglev trains in icy and snowy conditions. A numerical model was developed to simulate the train's operating conditions in these weather conditions, and factors such as crosswind, speed, and track type were analyzed for their impact on ice and snow accumulation on the train. Four application scenarios based on existing vehicle and track structure combinations were compared and analyzed, and specific optimization suggestions were proposed. Finally, based on the actual application conditions and analysis results, engineering application plans and related design points were presented. The conclusions drawn from the analysis had significant guiding significance for improving understanding of anti-icing technology for medium-low speed maglev trains and its engineering application.